Law enforcement identification of potential trafficking victims - Barrick, Kelle (Journal of crime and justice, 2021)
Since the passage of the Trafficking Victims Protection Act nearly 20 years ago, there have been relatively few human trafficking (labor or sex) arrests, charges, and convictions, which casts doubt among some on the magnitude of the problem. However, the absence of cases may not be because they do not exist, but rather because of the hidden nature of trafficking. In this study, we build on the existing literature on police awareness and understanding of sex trafficking by examining a random sample of law enforcement case files for prostitution and human trafficking-related offenses. We conducted descriptive quantitative and qualitative analyses to assess the extent and direction of law enforcement misidentification of sex trafficking cases as well as potential correlates. The results indicate that the misidentification of sex trafficking victims by law enforcement remains a challenge. Implications for policy and practice, as well as future research, are discussed.